Literary and visual representations of queer ecologies in South Africa’s maritime and terrestrial environments - Dimond, Harvey Lewis (University of the Witwatersrand, Johannesburg, 2023)
Not Available
A Research Report submitted in partial fulfilment of the requirements for the degree of Master of Arts, to the to the Faculty of Humanities at the School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Queer; Ecologies; Literature; Environment; South Africa; Literature; Visual art; UCTD; SDG-4: Quality education